2019
DOI: 10.1103/physrevd.99.066014
|View full text |Cite
|
Sign up to set email alerts
|

Holographic studies of the generic massless cubic gravities

Abstract: We consider the generic massless cubic gravities coupled to a negative bare cosmological constant mainly in D = 5 and D = 4 dimensions, which are Einstein gravity extended with cubic curvature invariants where the linearized excited spectrum around the AdS background contains no massive modes. The generic massless cubic gravities are more general than Myers quasi-topological gravity in D = 5 and Einsteinian cubic gravity in D = 4. It turns out that the massless cubic gravities admit the black holes at least in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 159 publications
(309 reference statements)
4
20
0
Order By: Relevance
“…The Kovtun-Son-Starinets bound on the ratio of entropy density to shear viscosity always holds [35], and small asymptotically flat black hole solutions were found to be stable [27], which may have implications for the information loss problem. Further holographic applications of this class of theories have been carried out, with discussions of the a-theorem, the universal stress-tensor two-point function and a universal relation for central charges [36][37][38]; more recently an extensive investigation of the holographic properties of the cubic case without massive modes was carried out, including holographic central charges, energy flux, Renyi entropies, and shear viscosity to entropy ratio [39]. Other recent work has shown that the shadows of GQG black holes have potentially interesting phenomenological signatures [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The Kovtun-Son-Starinets bound on the ratio of entropy density to shear viscosity always holds [35], and small asymptotically flat black hole solutions were found to be stable [27], which may have implications for the information loss problem. Further holographic applications of this class of theories have been carried out, with discussions of the a-theorem, the universal stress-tensor two-point function and a universal relation for central charges [36][37][38]; more recently an extensive investigation of the holographic properties of the cubic case without massive modes was carried out, including holographic central charges, energy flux, Renyi entropies, and shear viscosity to entropy ratio [39]. Other recent work has shown that the shadows of GQG black holes have potentially interesting phenomenological signatures [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Higher-curvature gravities satisfying this property -but not necessarily the GQTG condition eq. (8)-have been also studied in several other papers, e.g.,[28][29][30][31][32][33][34][35][36][37][38].…”
mentioning
confidence: 99%
“…Note that higher-curvature gravities satisfying property "1." -and not necessarily the rest of properties appearing in the list, nor condition (2.4)-have been studied in several other papers, e.g.,[20,26,27,[64][65][66][67][68][69][70][71].…”
mentioning
confidence: 99%